Dynamic Responsive Formation of Nanostructured Fibers in a Hydrogel Network: A Molecular Dynamics Study - Zidek, Jan; Milchev, Andrey; Jancar, Josef (Frontiers in Chemistry, 2020)
In an effort to study natural fiber formation such as, e.g., spider silk, we present a model, which is capable of forming biomimetic fibrillar nanostructure from a hydrogel micellar network. The latter consists of interacting atomic groups which form cores of micelles, and flexible chains forming the shells of the micelles. Micelles are connected in a compact network by linearly stretched chains. The structural elements of the network can be transformed during deformation from micellar type into fibrillar and their evolution is found to depend significantly on strain rate. Our model suggests a set of conditions suitable for the formation of nanostructured fibrillar network. It demonstrates that a fibrillar structure is only formed upon sufficiently fast stretching while, in contrast, the micellar gel structure is preserved, if the material is pulled slowly. We illustrate this key aspect by a minimalistic model of only four chains as part of the whole network, which provides a detailed view on the mechanism of fibril formation. We conclude that such a simplified structure has similar functionality and is probably responsible for the formation of nano-structured molecular fibrils in natural materials.